Female motivation to lead: the impact of same-sex role models and female leadership strength awareness - Boerner, Sabine; Schwarzmaier, Miriam; Tagos, Ioannis (Frontiers in Psychology, 2025)
IntroductionResearch on motivation to lead (MTL) suggests that women tend to be less motivated to take on leadership positions than men. By investigating female motivation to lead, we want to contest this finding.MethodsWe used five samples for validating our newly specified constructs (i.e., prosocial MTL and female leadership strength awareness) in Study 1 and a further sample of 248 students in Study 2.ResultsFirst, we propose a reconceptualization of MTL by introducing prosocial MTL as a fourth MTL type. We demonstrate that women have higher levels of prosocial MTL and non-calculative MTL, while men have higher levels of affective-identity MTL and social normative MTL. Second, we show that women are more strongly motivated to lead if they (a) have same-sex role models and (b) are aware of female strengths in leadership.DiscussionWe conclude that female motivation to lead is not necessarily lower than male motivation to lead but rather different in nature, and that it can be further enhanced by factors that seem particularly relevant for women.